Positive Peers Mobile Application Reduces Stigma Perception Among Young People Living With HIV. Issue 5 (September 2020) - Step, Mary M.; Knight, Kristina; McMillen Smith, Jennifer; Lewis, Steven A.; Russell, Theodore J.; Avery, Ann K.
Background . The burden of HIV-related stigma is associated with disparities in linkage to HIV care and viral suppression. The Positive Peers smartphone application aims to provide young people living with HIV with a supportive virtual community to counteract perceived stigma and better manage their illness.Method . A mixed-methods study that included a prospective survey and in-depth interviewing was conducted with young adults living with HIV, aged 13 to 34 years (n = 128). As part of a larger study, participants used the Positive Peers mobile application and reported demographic data, perceived stigma, and other psychosocial variables at enrollment, 6 months, and 12 months (n = 128). Select participants (n = 15) described their experiences in audio-recorded qualitative interviews. Verbatim transcripts were analyzed for potential themes and patterns.Results . A longitudinal multivariate model was developed to assess changes in stigma over the study period, overall, and with respect to participant characteristics. Baseline and 6-month stigma scores were higher for White and Other ethnicity persons relative to Black participants. At the 12-month time point, no statistical differences in stigma scores based on ethnicity were apparent. Interviews revealed Positive Peers as a nondiscriminatory community that offered a sense of belonging that appeared to have a restorative effect on negative self-image.Conclusions . Positive Peers provides a protected virtual space where young people living with HIV can converge in the common desire to support similar others. Mobile health applications that offer peer interaction may provide a persistent sense of belonging that neutralizes internalized stigmas in addition to benefits derived from application activity.